Self-regulation strategies and discursive competence at the higher level - Moreno Milla, Fiorella (2021)
From the exploration of previous studies, theories and concepts involved, in the following sections of this review paper, it is intended to manifest, in a conceptual and analytical way, the theme related to self-regulation strategies in the educational framework, to metacognition and self-regulation strategies, to communicative competence and discursive competence in the educational framework, to discursive competence in the academic text and, finally, to self-regulation strategies and written discursive competence of university students.